Perspectives of homeless veterans living with substance use disorders (SUD) and mental illness - Christian A. Betancourt; Debora G. Goldberg; Beth A. Hawks; Panagiota Kitsantas (Heliyon, 2023)
Upon returning home from the military, America's veterans face complex challenges such as homelessness and substance use disorders (SUD). Veterans who have experienced SUDs and homelessness are more likely to struggle with depression and suicidal behaviors. This study aims to understand homeless veterans' lived experiences of their everyday life and social interactions. We used semi-structured interviews to conduct a phenomenological study of 14 homeless veterans with known SUDs living in the Baltimore-Washington D.C. Metropolitan area. A Social-Ecological Model (SEM) was used to create themes, a priori, then used open coding analytic methods to identify emerging themes. Two-thirds of veterans used illicit drugs or abused alcohol, and nearly all reported a history of depression or anxiety. Suicidal behaviors were present in a third of all veterans. We found that veteran homelessness and substance use are strongly associated with emotional and physical trauma suffered while on active duty. Consequently, once homeless, a veteran's community may encourage and exacerbate SUDs, thus impeding a path toward sobriety. Homeless veterans who have struggled with SUDs and later experience a death in their family often relapse to substance use. Deeply exploring a veteran's relationships with family, friends, and their immediate community may reveal opportunities to address these issues using healthcare and community interventions.